Short-term monocular deprivation reduces inter-ocular suppression of the deprived eye. (August 2020) - Wang, Mengxin; McGraw, Paul; Ledgeway, Timothy
Abstract: The adult visual system was traditionally thought to be relatively hard-wired, but recent studies have challenged this view by demonstrating plasticity following short-term monocular deprivation. Depriving one eye of spatial information for 2–3 h increased subsequent sensory dominance of that eye. However, the mechanism underlying this phenomenon is unclear. The present study sought to address this issue and determine the consequences of short-term monocular deprivation on inter-ocular suppression of each eye. Sensory eye dominance was examined before and after depriving an eye of all input using an opaque patch for 2.5 h, in six adult participants with normal binocular vision. We used a percept tracking task during binocular rivalry (BR) to assess the relative eye dominance, and an objective probe detection task under continuous flash suppression (CFS) to quantify each eye's susceptibility to inter-ocular suppression. The monocular contrast increment threshold of each eye was also measured using the probe task to ascertain if the altered eye dominance is accompanied by changes in monocular perception. Our BR results replicated previous findings of a shift of relative dominance towards the eye that has been deprived of form information. More crucially, using CFS we demonstrated reduced inter-ocular suppression of the deprived eye with no complementary changes in the other eye, and no monocular changes in increment threshold. These findings imply that short-term monocular deprivation alters binocular interactions. The differential effect on inter-ocular suppression between eyes may have important implications for the use of patching as a therapy to recover visual function in amblyopia.